IMPROVEMENT OF STUDENT LEARNING ACTIVITY AND LEARNING ACHIEVEMENT USING THE PROBLEM-BASED LEARNING MODEL - Lia, Ade; Gunawan; Kusuma, Jaka Wijaya; Herawati, Rafika Asri (Yayasan Education and Social Center, 2024)
The research aims to improve the aspects of student learning activity and learning achievement using a problem-based learning model. This research is a collaborative Classroom Action Research (PTK). The subjects of this study are all grade IV students of SD Negeri 1 Dwuhan Kulon. The research was conducted in three cycles. During the learning process, observation of learning activity is carried out and at the end of each cycle, a test is carried out to determine the student's learning achievement. The data collection technique in this study uses tests, observation sheets, and documentation. The analysis of the research data consisted of the results of the learning achievement test, the observation of learning activity, and the improvement of both in each cycle. Presentation of data analysis in the form of graphs or diagrams. The results of the research obtained for the aspect of student learning activity in the first cycle reached a percentage of 57.89% with the category of quite good, the second cycle increased to 78.95% of the good category, and increased again in the third cycle of 89.47% of the very good category. The aspect of learning achievement increased each cycle by 53%, 73.3%, and 93.3%, respectively. It is concluded that the problem-based learning model can increase student learning activity and learning achievement appropriately